Pola Perilaku Hidup Bersih dan Sehat di Sekolah Dasar “SDN 02” Nyapah - Diana Romdhoningsih; Mohamad Ali; R. Bilqis Bunga Nirwana; Arnawati Arnawati; Saniati Saniati; Hera Damayanti; Nursaidah Ahmad; Fadilah Fadilah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Clean and Healthy Living Behavior is one of the targets for school children in educational institutions who must receive special attention in terms of PHBS. The population of children at school is a very large and important community. The function of health behavior is very necessary to promote clean and healthy living behavior as a rule for SD 02 Nyapah students which can then be applied in everyday life, especially for elementary school age children. This service research aims to determine patterns of clean and healthy living behavior at 02 Nyapah elementary school. In this writing we use descriptive research. The location of this service and research was carried out at SD 02 Nyapah, Nyapah Village, Walantaka District. The time for this service is 10 August 2024. The sample for this PHBS activity is 50 class 2 students. Based on the results of this research, it shows that elementary school children who have a high level of knowledge about PHBS are good, 96% of elementary school students' attitudes about PHBS are 95% good, and the actions of elementary school students in the category of 97% meet the requirements.